THE POSITION OF ARABIC LANGUAGE IN ADVANCING ISLAMIC CIVILIZATION AND SCIENCE - Usman Muzakki; Aziz Fauzan Akbar (Universitas Nahdlatul Ulama Lampung, 2020)
This research aims to clarify the role of Arabic in advancing Islamic science and civilization through library studies on the history of Arabic for a long time. The method used in this research is library research or library study by gathering literature and writing relatedrelated to the themes discussed. The results of this study are that: Arabic is the language that carries the most attributes. Besides being the language of the holy book of the Koran and Hadith, Arabic is the language of religion and Muslims. The position of Arabic as the language of Islamic science, language of education, and culture in the golden age of Islam was seen as important as a